Educational activity of folk schools in the south-east of Ukraine in XIX century (Pedagogy of Higher and Secondary Education, 2016)
Markiv V. N. Educational activity of folk schools in the south-east of Ukraine in XIX century.In ХІХ century there was a sharp contradiction between a demand for well-educated and prepared production workers and extraordinarily low level and backwardness from the modern requirements of all branches of education in the Russian empire of that time. The position of affairs in Ukraine were considerably worse, than in the central provinces of Russia. The imperial power, trying to retain people in obedience, used school for this purpose. The Russian-language studying made difficulties in understanding of learning material by Ukrainian-speaking children. Church patronage limited curricula and programs and did not give the access to new scientific knowledge, textbooks, articles and books.School and education of this period could not satisfy the necessities of people in training. Only at primary school the education was free of charge. But parents could not send their children to it as they have to work from childhood. Family could not provide their children with clothing, shoes, food. Rather high payment for studying in secondary (gymnasium) and high (universities) educational institutions was affordable only for noble families.Primary schools of Ukraine in that period were subjected to different ministries and departments, private persons, separate organizations. However, without regard to different subordination, content of education in them did not almost differ and determined by principles of Orthodoxy, autocracy, class, national and sexual inequality. Moreover a system of schools was not developed, and considerable part of children could not go to school.At primary schools students studied a law of God, Russian, arithmetic and singing. The position of affairs in the primary classes of province schools was not better.In the article the question of training of teaching staff for primary classes in XIX century is examined. At the end of XVIII beginning of XIX century there was an active process of colonization of North Black Sea region. New cities such as Kherson, Mykolaiv, Odesa and a lot of small towns and villages were built. Industry, trade, shipbuilding, agriculture were in progress. The first centers of education – folk schools were established, and the question of their teaching staff was actual.
Keywords: folk schools; teaching staff; branches of education; centers of education; pedagogical knowledge; «training of teachers»; professional teacher; primary school